Implementasi Supply Chain Management (SCM) Untuk Stok Dan Pendistribusian Barang Pada CV. Seloagro Berbasis Web - Alan Apriyan; Ahmad Fikri Zulfikar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
CV. Seloagro is a manufacturer and exporter of rattan wicker baskets from Indonesia. We are a company engaged in rattan wicker baskets and handicraft products. Currently our products have been marketed not only in Indonesia but also abroad. We manufacture and distribute all baskets to several countries. Therefore, here we need technology that can facilitate us in the search process for stock and goods that have been distributed. In the end we discovered web technology. Many advantages of web technology, among others, the information received is more effective and efficient. The problem formulation of this research is how to make a supply chain management information system for stock and distribution of goods for CV. Web-based Seloagro. The research method used is literature, observation, analysis, design, testing and implementation. This supply chain management information system for stock and distribution of goods is built using the PHP programming language and utilizes the MySQL database as a database server. The result of this study is the implementation of a supply chain management program for the stock and distribution of these goods, it is hoped that later the search process for stock and goods that have been distributed can run quickly, so that work is more efficient and effective. The management can directly find out the report on the stock process and the distribution of goods directly, because the program created by the management can access the program directly to view stock reports and the distribution of goods.